2021
DOI: 10.1038/s41586-021-04017-w
|View full text |Cite
|
Sign up to set email alerts
|

Fc-engineered antibody therapeutics with improved anti-SARS-CoV-2 efficacy

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 39 publications
9
140
3
Order By: Relevance
“…The genetic loss of NKG2C (a hallmark of adaptive NK cells, capable of enhanced ADCC) is also a risk factor for severe disease 4 , implying a protective role in COVID19 infection. In support of this, in animal models, Fc-mediated functions correlate with protection in vaccination 5 , and monoclonal antibody-mediated control of SARS-CoV2 infection is enhanced by Fc-dependent mechanisms 611 , which enable control of disease even in the absence of neutralising activity 12 . Furthermore, although neutralising monoclonal antibodies are effective when administered prophylactically, Fc-activity is required for efficacy when administered to animals therapeutically 11 .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The genetic loss of NKG2C (a hallmark of adaptive NK cells, capable of enhanced ADCC) is also a risk factor for severe disease 4 , implying a protective role in COVID19 infection. In support of this, in animal models, Fc-mediated functions correlate with protection in vaccination 5 , and monoclonal antibody-mediated control of SARS-CoV2 infection is enhanced by Fc-dependent mechanisms 611 , which enable control of disease even in the absence of neutralising activity 12 . Furthermore, although neutralising monoclonal antibodies are effective when administered prophylactically, Fc-activity is required for efficacy when administered to animals therapeutically 11 .…”
Section: Introductionmentioning
confidence: 80%
“…In animal models of vaccination 5 and monoclonal antibody administration 69,11 against SARS-CoV2, antibody-mediated activation of cellular immunity is a critical component of the protective immune response. However, inflammation dominates severe COVID-19 disease 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the ADE effect is generally overlooked, we suggest that a careful selection, engineering and optimization of immunoglobulin Fc domains that offer improved potency and safer routes be considered. For instance, Yamin et al [181] and Pinto et al [182] have exceptionally demonstrated approaches to circumvent detrimental immunopathology, which may prove helpful for avidity-inspired therapeutics.…”
Section: Avidity-inspired Nanobody Therapeutics: Outlookmentioning
confidence: 99%
“…The role of the interaction between the Fc portion of antibodies and the Fc receptors can also be evaluated in the transgenic mouse models ( 58 ). Interactions between Fc and FcγR are required for in vivo protective activity of neutralizing anti–SARS-CoV-2 mAbs by comparing the efficacy of the antibody treatment in animals expressing the human FcγR versus genetically defined FcγR-null mice.…”
Section: Session 2 Key Theme: Preclinical Delivery Pharmacology and Efficacy Of Anti–sars-cov-2 Antibodiesmentioning
confidence: 99%
“…Interactions between Fc and FcγR are required for in vivo protective activity of neutralizing anti–SARS-CoV-2 mAbs by comparing the efficacy of the antibody treatment in animals expressing the human FcγR versus genetically defined FcγR-null mice. Furthermore, Fc domain variants engineered for selectively enhanced binding to activating FcγRs exhibit improved efficacy using the SARS-CoV-2 mouse-adapted model ( 58 ). The Collaborative Cross mice, a recombinant inbred mouse strain ( 59 , 60 ), have been valuable in addressing the natural genetic variation linked to SARS-CoV-2 pathogenesis.…”
Section: Session 2 Key Theme: Preclinical Delivery Pharmacology and Efficacy Of Anti–sars-cov-2 Antibodiesmentioning
confidence: 99%